ANALISIS RASIO CAPITAL ADEQUACY RATIO, LOAN DEPOSIT RATIO DAN BOPO TERHADAP PROFITABILITAS PADA BANK PERKREDITAN RAKYAT - Hutri Agus Romi (Postgraduate Management Journal, 2022)
The purpose of this study was to determine the CAR (Capital Adequacy Ratio), LDR (Loan Deposit Ratio) and BOPO simultaneously or partially responsible for a significant to ROA (Return on Asset) at Bank Perkreditan Rakyat in Batam period 2011-2015.The research sample was determined by using purposive sampling method so obtained 14 samples of 27 and used secondary data from published financial statements at banking in www.ojk.go.id. Data analysis was done quantitatively in terms of multiple regression and the classical assumption test and processed with SPSS 21 (statistical package for social science). The results showed that the CAR (Capital Adequacy Ratio), LDR (Loan Deposit Ratio) and BOPO simultaneously significant effect on ROA (Return on Assets).The T- test results showed partial BOPO significant effect on ROA (Return on Assets) but CAR (Capital Adequacy Ratio) and LDR (LoanDeposit Ratio) had no significant effect on ROA (Return on Asset).